Metabolic cost of human hopping - Gutmann, A. K.; Bertram, J. E. A. (The Journal of Experimental Biology, 2017)
To interpret the movement strategies employed in locomotion, it is necessary to understand the source of metabolic cost. Muscles must consume metabolic energy to do work, but also must consume energy to generate force. The energy lost during steady locomotion and, hence, the amount of mechanical work muscles need to perform to replace it can be reduced and, in theory, even eliminated by elastically storing and returning some portion of this energy via the tendons. However, even if muscles do not need to perform any mechanical work, they still must generate sufficient force to tension tendons and support body weight. This study shows that the metabolic cost per hop of human hopping can largely be explained by the cost of producing force over the duration of a hop. Metabolic cost determined via oxygen consumption is compared with theoretical predictions made using a number of different cost functions that include terms for average muscle work, force, force rate and impulse (time integral of muscle force). Muscle impulse alone predicts metabolic cost per hop as well as more complex functions that include terms for muscle work, force and force rate, and explains a large portion (92%) of the variation in metabolic cost per hop. This is equivalent to 1/effective mechanical advantage, explaining a large portion (66%) of the variation in metabolic cost per time per unit body weight. This result contrasts with studies that suggest that muscle force rate or muscle force rate per time determines the metabolic cost per time of force production in other bouncing gaits such as running.